Systematic literature review of the use of Staff Attitudes to Coercion Scale (SACS) - Husum, Tonje Lossius; Siqveland, Johan; Ruud, Torleif; Lickiewicz, Jakub (Frontiers in Psychiatry, 2023)
Objective: Staff’s attitudes to the use of coercion may influence the amount of coercive interventions employed and staff willingness to engage in professional development projects aimed at reducing the use of coercion itself. The Staff Attitude to Coercion Scale (SACS) was developed to assess the attitudes of mental health care staff to the use of coercion in 2008 and has been employed subsequently. This global study systematically reviews and summarizes the use of the scale in research. Method: Seven databases were searched for studies using SACS in articles published in peer reviewed journals and grey literature. In addition, researchers who have asked for permission to use the scale since its development in 2008 were contacted and asked for their possible results. Extracting of data from the papers were performed in pairs of the authors. Results: Of the 82 identified publications, 26 papers with 5838 respondents were selected for review. A review of the research questions used in the studies showed that the SACS questionnaire was mostly used in studies of interventions aimed at reducing coercion and further explain variation in the use of coercion. Conclusion: SACS is, to our best of knowledge, the only questionnaire measuring staff’s attitudes to the use of coercive interventions in mental health services. Its widespread use also indicates that this tool is perceived as feasible and useful as well as demonstrating the need for such a tool. However, further research is needed as the relationship between staff attitudes to coercion and the actual use of coercion also remains unclear and needs to be further investigated. Staff attitudes to coercion may be a prerequisite for leaders and staff in MHC to engage in service development and quality improvement projects.